2019
DOI: 10.4236/cus.2019.73020
|View full text |Cite
|
Sign up to set email alerts
|

From Msimbazi River Valley to Mabwepande Settlement: The Resettlement Process and Its Challenges

Abstract: The paper documents the resettlement process undertaken following the 2011 heavy rains in Dar es Salaam City, which adversely affected many people who lived in flood prone areas particularly in and along Msimbazi river valley. Within the resettlement process, challenges which were encountered by different actors during the resettlement process were investigated. With the use of qualitative and quantitative data, the paper shows that the resettlement of households from Msimbazi River Valley to Mabwepande follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…As a result, they have no plans to leave the settlement, for they hope the government will provide solutions to flooding. John et al (2019) revealed consistent findings in Tanzania where, following the flood incidences of 2011, floodaffected victims were relocated to Mabwepande settlement, on the outskirts of Dar es Salaam City. However, some returned to the original settlement because of inadequate facilities provided by the government to meet their livelihoods (John et al, 2019: 402).…”
Section: Residents In Flood-risk Informal Settlementssupporting
confidence: 70%
“…As a result, they have no plans to leave the settlement, for they hope the government will provide solutions to flooding. John et al (2019) revealed consistent findings in Tanzania where, following the flood incidences of 2011, floodaffected victims were relocated to Mabwepande settlement, on the outskirts of Dar es Salaam City. However, some returned to the original settlement because of inadequate facilities provided by the government to meet their livelihoods (John et al, 2019: 402).…”
Section: Residents In Flood-risk Informal Settlementssupporting
confidence: 70%
“…International frameworks, such as the Sendai Framework for Disaster Risk Reduction 2015–2020 (SFDRR), are meant to encourage the development of public policies from the national down to the local level to address relocations of communities in disaster-prone areas (United Nations International Strategy for Disaster Reduction [UNISDR], 2015 ). Countries such as Fiji (Republic of Fiji, 2017 ) and Kiribati (Klepp & Herbeck, 2016 ), for example, have developed guidelines to support proactive resettlement, and John et al ( 2019 ) argue for the strengthening of governing institutions responsible for implementing such plans. However, as noted by others (van Niekerk et al, 2020 ) implementing policies with targets measured against international frameworks such as the SFDRR require understanding the contextual historical and socioeconomic environment that influences the outcomes.…”
Section: Contextualising “Resettlement”: Experiences Institutional Shortcomings and Political Ecologymentioning
confidence: 99%
“…Reckless and haphazard resettlement of communities places them in the same or more dangerous conditions than they were before. John et al ( 2019 ) observed that in Tanzania, the Mabwepande community resettled by the government due to floods, found themselves in an area with massive soil erosion actually increasing the risk of the floods inundating some of the houses.…”
Section: Contextualising “Resettlement”: Experiences Institutional Shortcomings and Political Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the catchment has been a subject of increased floods in recent years (Sauka, 2019). Severe floods were reported in 2009, 2010, 2014, 2015, 2017, 2018, 2019(John et al, 2019Kironde, 2016;Sauka, 2019;Valimba & Mahe, 2020), exposing the city's vulnerability to climatic events. The floods are associated with heavy rains (Valimba & Mahe, 2020), whereby within a few hours of the rain event the water rises to a height of two meters or more above the banks of the river.…”
Section: Introductionmentioning
confidence: 99%